Severe Cutaneous Adverse Drug Reactions at a Tertiary Care Center in Saudi Arabia - Mohammed I. AlJasser (Hindawi Limited, 2023)
Background. Severe cutaneous adverse drug reactions (SCARs), although rare, are known to be associated with significant morbidity and mortality. SCARs include drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN), and acute generalized exanthematous pustulosis (AGEP). Studies on SCARs are limited in Saudi Arabia. This study aims to characterize SCARs at a tertiary care center in Saudi Arabia. Methods. A cross-sectional study was conducted at King Abdulaziz Medical City, Riyadh, Saudi Arabia. All inpatient and emergency department consultations to dermatology were electronically reviewed during the period from January 2016 to December 2020. All patients who developed an adverse cutaneous drug reaction were enrolled. Detailed analysis was performed only for SCARs. The culprit medication was determined based on the latency period, history of previous intake of the medication, and drug notoriety. Results. There were 3050 hospital consultations to dermatology during the study period. Cutaneous adverse drug reactions constituted 253 (8.3%) cases. A total of 41 patients with SCARs were identified, accounting for 16.2% of all cutaneous drug reactions. Antibiotics and anticonvulsants were the most common causative drug groups accounting for 28 (68.3%) and 9 (22%) cases, respectively. DRESS was the most common SCAR. The latency period was the longest for DRESS and shortest for AGEP. Vancomycin was responsible for approximately a third of DRESS cases. Piperacillin/tazobactam was the most common cause for SJS/TEN and AGEP. The majority of drugs causing AGEP were antibiotics. The mortality rate was the highest in SJS/TEN (5/11 (45.5%)), followed by DRESS (1/23 (4.4%)) and AGEP (1/7 (14.3%)). Conclusion. SCARs are rare in Saudis. DRESS appears to be the most common SCAR in our region. Vancomycin is responsible for most cases of DRESS. SJS/TEN had the highest mortality rate. More studies are required to further characterize SCARs in Saudi Arabia and Arabian Gulf countries. More importantly, thorough studies of HLA associations and lymphocyte transformation tests among Arabs with SCARs are likely to further improve patient care in the Arabian Gulf region.